Selective labelling and eradication of antibiotic-tolerant bacterial populations in Pseudomonas aeruginosa biofilms - Song Lin Chua (Nature Portfolio, 2016)
Pathogenic bacteria can aggregate to form biofilms and develop tolerance to antibiotics. Here, the authors use a proteomics approach to study the development of tolerance to the antibiotic colistin in Pseudomonas aeruginosabiofilms, and show that co-treatment with a second compound kills the tolerant cells.